Effect of far infrared heating process on surface decontamination and quality attributes of whole yellow and white onions. (December 2021) - Coskun, Eda; Ozturk, Samet; Akpinar, Merve; Halkman, A. Kadir; Erdogdu, Ferruh
Abstract: This study aimed to develop an effective decontamination process for whole yellow and white onions with maintained quality attributes. For this purpose, a far infrared radiation (FIR) process was evaluated to determine its effects on microbial safety and quality of the onions. Prior to the FIR process, samples were inoculated with Salmonella culture to about 7–8 log10  CFU/cm 2 and stored for 1–48 h at room temperature. Inoculated samples were then processed up to 120 s at 400 °C infrared source temperature. Temperature chance of the onions was recorded by using T-type thermocouples, and surface temperature distribution was obtained with an infrared thermal camera. Quality attributes (color changes, mass losses and textural changes) were also evaluated following the FIR process. The results indicated that 3.3 and 2.4 log10  CFU/cm 2 reductions in the Salmonella counts were obtained for the whole yellow and white onions, stored for 1 h at room temperature after 120 s FIR processing. The background microbial population on the outer skin of the onions was under the detection limit (<1 log10  CFU/g). It was observed that the effectiveness of FIR treatment on Salmonella decontamination decreased as the storage time increased from 1 to 48 h at room temperature. FIR process did not significantly affect the quality attributes of the onions, and the results confirmed the potential use of FIR process for surface decontamination of the onions. Further studies were suggested to design an effective FIR system for industrial scale applications. Highlights: More than 2-log reduction in Salmonella were obtained at 400 °C FIR temperature. Low aw increased surface adaptation of Salmonella and affected process efficiency. FIR decontamination process did not affect the quality attributes of onions. FIR processing for surface decontamination of onions was confirmed.